1979
DOI: 10.1152/ajprenal.1979.236.4.f357
|View full text |Cite
|
Sign up to set email alerts
|

Voltage dependence of calcium transport in the thick ascending limb of Henle's loop

Abstract: Thick ascending limbs of Henle's loop were dissected from rabbit kidneys and perfused in vitro. Unidirectional transepithelial calcium fluxes from lumen-to-bath and bath-to-lumen were measured with 45Ca using different solutions that caused the transepithelial voltage to vary over a wide range. With lumen-positive voltages there was net calcium absorption from lumen to bath which varied directly with the voltage. With voltage near zero there was no measurable net flux. When the voltage was made negative, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 0 publications
6
34
0
Order By: Relevance
“…Our data on calcium transport are qualitatively similar to those previously published by Bourdeau and Burg (13,22). Measuring net transport with the electron probe rather than unidirectional fluxes, we found that calcium transport was strongly voltage dependent and enhanced by large doses of PTH; however, regression analysis of net calcium transport vs. voltage revealed a slope significantly steeper than that reported by these authors.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our data on calcium transport are qualitatively similar to those previously published by Bourdeau and Burg (13,22). Measuring net transport with the electron probe rather than unidirectional fluxes, we found that calcium transport was strongly voltage dependent and enhanced by large doses of PTH; however, regression analysis of net calcium transport vs. voltage revealed a slope significantly steeper than that reported by these authors.…”
Section: Resultssupporting
confidence: 90%
“…In these series of experiments the effects of a wide variety of transepithelial PD on net transport rates of calcium, magnesium, and potassium were studied. To achieve a wide range of positive and negative luminal potentials with respect to the bath, we took advantage of the ionic and permeability properties of this segment, similar to previously reported studies by Bordeau and Burg (13).…”
Section: Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Precautions taken to prevent loss of 45Ca-counts included the following: (a) To prevent binding of calcium to glass, all pipettes in contact with perfused or collected fluid were siliconized with SC-87 (Pierce Chemical Co., Rockford, IL); (b) All oils used were waterequilibrated and bubbled with 100% CO2 to prevent loss of C02, alkalinization of fluid samples, and precipitation of calcium salts; (c) Collected samples were expelled from the constant-volume constriction pipette with a 10-mM EGTA solution to ensure complete removal of 45Ca; and (d) All counting vials contained two drops of 12 N HCO to acidify the scintillation fluid and prevent loss of counts with time (14). In previous studies, the above maneuvers were sufficient to prevent binding of isotopic calcium from static solutions in the pipettes for at least 2 h. Furthermore, recovery of isotopic calcium in the bath closely matches that which disappears from the perfusate (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…The basic approach used to determine Ca permeability involved construction of a transepithelial gradient of NaCl (56). To clamp for Vte, asymmetric solutions were used: the tubule was bathed with a solution containing 144 mmol/l Na and 120 mmol/l Cl, whereas the lumen was perfused with a solution containing 53 mmol/l Na and 29 mmol/l Cl.…”
Section: Measurement Of Transepithelial Permeability To Camentioning
confidence: 99%